2012
DOI: 10.1073/pnas.1214682110
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor YY1 is essential for regulation of the Th2 cytokine locus and for Th2 cell differentiation

Abstract: The Th2 locus control region (LCR) has been shown to be important in efficient and coordinated cytokine gene regulation during Th2 cell differentiation. However, the molecular mechanism for this is poorly understood. To study the molecular mechanism of the Th2 LCR, we searched for proteins binding to it. We discovered that transcription factor YY1 bound to the LCR and the entire Th2 cytokine locus in a Th2-specific manner. Retroviral overexpression of YY1 induced Th2 cytokine expression. CD4-specific knockdown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 53 publications
5
56
0
Order By: Relevance
“…We also showed that YY1 does not compensate the loss of GATA3 in driving Th2 cytokine expression in Th1 cells. 4 These results support the idea that YY1's role in Th2 differentiation is that of organizing chromatin structure rather than direct transcriptional activation.…”
Section: Yy1 As a Direct Transcriptional Activatorsupporting
confidence: 80%
See 2 more Smart Citations
“…We also showed that YY1 does not compensate the loss of GATA3 in driving Th2 cytokine expression in Th1 cells. 4 These results support the idea that YY1's role in Th2 differentiation is that of organizing chromatin structure rather than direct transcriptional activation.…”
Section: Yy1 As a Direct Transcriptional Activatorsupporting
confidence: 80%
“…5 It has been shown to interact with many transcription factors, chromatin co-activators, and co-repressors. 5 In our previous study, we showed that knockdown of YY1 caused a reduction of intrachromosomal interactions between the Th2 LCR and the Il4 promoter, 4 suggesting that YY1 plays a role in this process. Long-range chromosomal interactions are important for regulation of gene transcription and genome maintenance.…”
Section: Role Of Yy1 In Chromosomal Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nfil3 (E4BP4), a transcription factor that is critical for the development of NK cells and ILCs 137142 , is highly expressed by Th2 cells and responsible for regulating IL-10 production 143 . In addition, YY1 physically interacts with GATA3 and thus collaborates with GATA3 in chromatin remodeling and cytokine production 144 .…”
Section: Key Transcription Factors Required For Th2 Cell Differentmentioning
confidence: 99%
“…Using a TF-binding database and EMSA, YY1 was discovered as a candidate binding protein . The specifi c binding was confi rmed by antibody-supershift antibodies and oligonucleotide competition experiments [ 52 ].…”
Section: Electrophoretic Mobility Shift Assay (Emsa)mentioning
confidence: 99%